Dam impoundment elevates soil phosphorus and some trace elements in reservoir hydro‐fluctuation belts. Issue 2 (31st August 2022) - Yang, Dan; Xie, Zongqiang
Abstract: To examine the role of dam impoundment in elevating the levels of soil‐associated phosphorus (P) and trace elements in reservoir hydro‐fluctuation belts (RHB), soil samples in RHB and adjacent uplands (non‐flooded area, NFA) in the Three Gorges Reservoir, China, were collected and analyzed. Concentrations of available P, copper (Cu), chromium (Cr), and zinc (Zn) were found to be higher in RHB than in NFA ( p < .05), whereas organic carbon was comparable in RHB and NFA ( p > .05). The elevated levels of Cu, Cr, and Zn in RHB were probably associated the repeated drying–rewetting cycles created by the dam impoundment. The 95th percentile of the single‐factor pollution index and geo‐accumulation index in RHB were 1.29 and −0.21 for Zn, 3.21 and 1.15 for Cu and 3.37 and 1.17 for Cr. Elevated pollution potential of soil‐associated Zn, Cu, and Cr existed in RHB of the Three Gorges Reservoir. Core Ideas Dam impoundments decreased total C and total N concentrations in reservoir flooded soils. Cu, Zn, and Cr concentrated in the reservoir flood areas. Variability of Cu, Zn, and Cr was captured in single‐factor pollution index and geo‐accumulation index Abstract : Distribution and probabilistic risk of Cu, Cr, and Zn after dam impoundment.